Informal Care and Long-term Labor Market Outcomes - Hendrik Schmitz; Matthias Westphal (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
In this paper we estimate long-run effects of informal care provision on female caregivers' labor market outcomes. We assess effects up to eight years after care provision and, thereby, complement the previous literature that focuses on short-run-effects. We compare a static version, where average effects of care provision in a certain year on later labor market outcomes are estimated, to a partly dynamic version where the effects of up to three consecutive years of care provision are analyzed. Our results suggest that there are significant initial negative effects of informal care provision on the probability to work full-time. The reduction in the probability to work full-time by 4 percentage points is persistent over time. Effects on the probability of being in the labor force are quite small, however, high care intensity strongly reduces the probability to be in the labor force eight years after the start of the episode. Short-run effects on hourly wages are zero but we find considerable long-run wage penalties. All in all, we find considerable negative labor market effects even several years the end of informal care provision.
Keywords: J22; I10; J14; 330